answersLogoWhite

0

use the chain rule and product rule: f(x)=1/u(x), f'(x)=-1/u2(x)*u'(x) and f(x)=a(x)b(x), f'(x)=a'(x)b(x)+b'(x)a(x)

the derivative of sin is cos, and the derivative of cos in negative sin.

so f(x)=1/(sin(x)cos(x)), f'(x)=-1/(sin(x)cos(x))2*(cos2(x)-sin2(x))

or assume sin(x)cos(x)=.5sin(2x)

so using chain rule, f'(x)=-2/sin2(2x)*.5cos(2x)*2. Both answers are equivalent.

User Avatar

Wiki User

16y ago

Still curious? Ask our experts.

Chat with our AI personalities

BlakeBlake
As your older brother, I've been where you are—maybe not exactly, but close enough.
Chat with Blake
EzraEzra
Faith is not about having all the answers, but learning to ask the right questions.
Chat with Ezra
FranFran
I've made my fair share of mistakes, and if I can help you avoid a few, I'd sure like to try.
Chat with Fran

Add your answer:

Earn +20 pts
Q: What is the derivative of 1 divided by sinx cosx?
Write your answer...
Submit
Still have questions?
magnify glass
imp